On the synonymy between paraponychus corderoi (baker & pritchard, 1962) and p. incanus gonzález & flechtmann, 1977 (acari, tetranychidae) - Hernandes, Fabio Akashi [UNESP]; Feres, Reinaldo J. [UNESP]; Flechtmann, Carlos H.W. (Systematic and Applied Acarology Society, 2011)
In this paper we propose a new synonymy between P. corderoi (Baker & Pritchard, 1962) and P. incanus González & Flechtmann, 1977, based on the examination of type-specimens.© Systematic & Applied Acarology Society.